The Degree-Topology of CertainTypes of Graphs and PT0-Space - Hameed, Zainab Naji; Kadhem, Hiyam Hassan (Iraqi Journal of Science, 2024)
This work aimed to study the degree topology of certain types of graphs namely, the wheel, helm, gear, pan, tadpole, and windmill graphs, respectively. In addition, a new separation axiom known as -space that joins the topological space and paths in the graph is introduced. Also, the relation between -space and the degree-topology of the connected and disconnected graph was stydied. Moreover, many examples were studied in new separation space.